2010
DOI: 10.1038/cddis.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of nitric oxide delay the differentiation of embryonic stem cells and promote their survival

Abstract: Nitric oxide (NO) is an intracellular messenger in several cell systems, but its contribution to embryonic stem cell (ESC) biology has not been characterized. Exposure of ESCs to low concentrations (2–20 μM) of the NO donor diethylenetriamine NO adduct confers protection from apoptosis elicited by leukaemia inhibitory factor (LIF) withdrawal. NO blocked caspase 3 activation, PARP degradation, downregulation of the pro-apoptotic genes Casp7, Casp9, Bax and Bak1 and upregulation of the anti-apoptotic genes Bcl-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 39 publications
2
56
0
1
Order By: Relevance
“…Sinomenine (or cocculine) is a morphine derivative with anti-rheumatic effects thought to be primarily mediated via the release of histamine (Yamasaki, 1976); but other effects such as inhibition of prostaglandin, leukotriene and NO synthesis may also be involved (Liu et al, 1994). An unrelated study has shown that exposure of ESCs to low concentrations of diethylenetriamine NO (DETA-NO) adduct maintains hESC pluripotency to a similar extent as bFGF (Tejedo et al, 2010), although no definitive mechanism was provided. Gatifloxacin is an antibiotic of the fourth-generation fluoroquinolone family (Burka et al, 2005), while flurbiprofen is a member of the phenylalkanoic acid derivative family of non-steroidal antiinflammatory drugs (NSAIDs) used to treat the inflammation and pain of arthritis.…”
Section: Other Modifiers Of Pluripotencymentioning
confidence: 99%
See 1 more Smart Citation
“…Sinomenine (or cocculine) is a morphine derivative with anti-rheumatic effects thought to be primarily mediated via the release of histamine (Yamasaki, 1976); but other effects such as inhibition of prostaglandin, leukotriene and NO synthesis may also be involved (Liu et al, 1994). An unrelated study has shown that exposure of ESCs to low concentrations of diethylenetriamine NO (DETA-NO) adduct maintains hESC pluripotency to a similar extent as bFGF (Tejedo et al, 2010), although no definitive mechanism was provided. Gatifloxacin is an antibiotic of the fourth-generation fluoroquinolone family (Burka et al, 2005), while flurbiprofen is a member of the phenylalkanoic acid derivative family of non-steroidal antiinflammatory drugs (NSAIDs) used to treat the inflammation and pain of arthritis.…”
Section: Other Modifiers Of Pluripotencymentioning
confidence: 99%
“…Antimycin A Mitochondrial respiratory chain (Varum et al, 2009) BIO GSK3b (Bone et al, 2009;James et al, 2005;Sato et al, 2004) Butyryl CoA Energy release/storage (Ware et al, 2009) CHIR99021 GSK3b (Tsutsui et al, 2011) DETA-NO NO donor (Tejedo et al, 2010) Dorsomorphin ALK2, 3 and 6 (Gonzalez et al, 2011) EHNA ? (Burton et al, 2010a,b) FBP ?…”
Section: Drug Target Referencementioning
confidence: 99%
“…Murine bone marrow stromal (OP9) cell apoptosis was reduced in cells treated with the NO donor S-nitroso-N-acetylpenicillamine or YC-1 (300). In embryonic stem cells, treatment with low concentrations of an NO donor delayed the process of differentiation and maintained expression of the key self-renewal transcription factors: octamer-binding transcription factor 4 (Oct4), Nanog, and sex determining region Y-box 2 (Sox2) (270). Hematopoietic stem cell sensitivity to the self-renewal effects of NO may decrease with cell age (99).…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 99%
“…Thus, treatment of mouse and human ES cells with 2 μM DETA-NO protects them from apoptosis induced by cell differentiation by upregulating the expression of anti-apoptotic genes, such as Bcl2, Bcl2-l and Birc6; by downregulating pro-apoptotic genes, such as Casp7, Casp9, Bax and Bak1; and by inhibiting caspase-3 activation by cleavage. 114 Several mechanisms have been described for the antiapoptotic actions of NO, such as protein activation by modification of prosthetic groups 102,115 and cysteine modification by S-nitrosylation. 29,111,112,[116][117][118] Both mechanisms can regulate signaling pathways 17,101,102,104 and gene expression.…”
Section: Nitric Oxide As a Survival Molecule In Pancreatic β-Cellsmentioning
confidence: 99%